The role of the Quadrilateral Security Dialogue in building the security architecture in Southeast Asia - Dvořáčková, Kristýna (2025)
The thesis examines the role of the Quadrilateral Security Dialogue (Quad) in the development of Southeast Asia's security architecture using the theory of offensive realism. The thesis addresses the questions of whether the Quad can be integrated into existing Southeast Asian security architecture, what internal and external factors limit its effectiveness, and how the Quad affects the regional balance of power. The first part focuses on the theory and key concepts. The second part analyses the security architecture of Southeast Asia. The third part analyzes the motives of dialogue members and their perspectives on the region. The last section examines how dialogue affects the balance of power in the region.